2008
DOI: 10.1371/journal.pone.0001394
|View full text |Cite
|
Sign up to set email alerts
|

Using fMRI Brain Activation to Identify Cognitive States Associated with Perception of Tools and Dwellings

Abstract: Previous studies have succeeded in identifying the cognitive state corresponding to the perception of a set of depicted categories, such as tools, by analyzing the accompanying pattern of brain activity, measured with fMRI. The current research focused on identifying the cognitive state associated with a 4s viewing of an individual line drawing (1 of 10 familiar objects, 5 tools and 5 dwellings, such as a hammer or a castle). Here we demonstrate the ability to reliably (1) identify which of the 10 drawings a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
155
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 32 publications
14
155
2
Order By: Relevance
“…High classification accuracies for the two categories [Shinkareva et al, 2008] have been previously shown for the whole brain (single large scale ROI). In this work we are introducing the analysis of interobject distances based on the whole brain (single large scale ROI).…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…High classification accuracies for the two categories [Shinkareva et al, 2008] have been previously shown for the whole brain (single large scale ROI). In this work we are introducing the analysis of interobject distances based on the whole brain (single large scale ROI).…”
Section: Introductionmentioning
confidence: 59%
“…The RV-coefficient has been previously used in the neuroimaging literature [Abdi et al, 2009;Glascher et al, 2009;Kherif et al, 2003;O'Toole et al, 2007;Shinkareva et al, 2006Shinkareva et al, , 2008 and is described in detail in Abdi [2007] and Ramsay et al [1984]. It measures the overall similarity of two matrices and is analogous to a squared coefficient of correlation.…”
Section: Similarities In Interobject Distancesmentioning
confidence: 99%
See 3 more Smart Citations